Constructing portable depth from defocus optical profilometers for surface roughness evaluation. (30th January 2015) - Klein, Robert; Steiner, Matthew; Suhring, William; Agnew, Sean; Fitz-Gerald, James
Abstract: Hand portability of non-contact optical profilometers represents a significant technological breakthrough for wide-area industrial processes such as grit blasting, capable of replacing mechanical styluses and providing real time assessment of surface roughness without damaging sampled areas. This paper demonstrates the possibility of building depth from defocus profilometers using off the shelf components, allowing for improved portability, affordability, and customization compared to similar table-top commercial products. An outlined demonstration device is proven to be capable of matching the performance of an ISO/NIST standardized mechanical profilometer for isotropic rough surfaces in the 2–10 μ m R a range with R 2 > 0.96, and important considerations for each component of the assembly are addressed in detail. A prototype for a next generation liquid-lens based depth from defocus optical profilometer is also presented along with the technological obstacles found to be associated with such devices.